Usability in IPC Price Collection Application: Evaluation of Interface and User Experience - Brito, Lívio Fagundes; Barbosa, Ingridh Igreja de Salles; Silva, Marcos Henrique Alves da; Drumond, Carlos Eduardo; Melo, Rodrigo Massao Y. de Albuquerque; Guedes, Dyeggo Rocha; Simões, Jorge Eduardo Macedo; Sousa, Léia Sousa de (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: Price collection is essential for economic analyses and inflation monitoring. Problem: The traditional price collection method requires significant effort from researchers and often results in inconsistencies and formatting issues, impacting the accuracy of generated inflation indexes and increasing the data correction time. Proposed Solution: To mitigate these issues, a mobile price collection application was developed to automate and standardize data entry. Additionally, a usability analysis of the application is presented. Information Systems Theory: This work is based on the Boundary Object Theory, considering the application as a connection point between different user profiles, and on the Behavioral Decision Theory, which guides the design to minimize cognitive biases in data collection. Method: Usability tests proposed by the authors were conducted, along with the System Usability Scale (SUS), a method from the literature, for quantitative and qualitative analyses of user experience evaluation and system accuracy. Results Summary: The results show high acceptance and accuracy in the use of the application, with reduced errors and time in data collection. Findings indicated reliable consistency in usability evaluations and pointed to areas for improvement. Contributions and Impact on the Information Systems Area: This research demonstrates the positive impact of automation in economic data collection and reinforces the application of IS theories in interface design. The work contributes to usability studies and offers a model for standardizing collection processes that is applicable to various economic monitoring contexts.